Buried dermal flap for the treatment of chronic postoperative seroma. (26th August 2010) - Nayak, Nikhil; Narayan, Deepak
Abstract : Postoperative seroma is a common postoperative complication, particularly following surgery on massive weight loss patients. Within this patient population, seromas are often chronic, requiring multiple invasive procedures to adequately control. Here, the authors describe a unique dermal flap approach for the long-term treatment of postoperative seroma.